PENGARUH STATUS PARTISIPASI DALAM PELAYANAN KESEHATAN DASAR (POSYANDU) TERHADAP STATUS GIZI BALITA DI PONKESDES MLAJAH BANGKALAN - Alis Nur Diana; Lelly Aprilia Vidayati; Siti Rochimatul Lailiyah (Jurnal Medicare, 2025)
Nutritional status describes the body's condition resulting from food intake and nutrient use, which is vital for energy, growth, tissue repair, and physiological function. A preliminary study at Ponkesdes Mlajah Bangkalan found that among 10 mothers with toddlers suffering from poor nutrition, 80% of the children did not actively attend the posyandu, while 20% did. This study aimed to examine the effect of participation in basic health services (posyandu) on toddlers’ nutritional status. Using an observational analytic design with a cross-sectional approach, 143 respondents (from 227) were selected through Stratified Simple Random Sampling. The independent variable was posyandu participation status; the dependent variable was toddler nutritional status. Data were collected using Islamic boarding school cohort records and Z-score applications, and analyzed using the Spearman Rank test (Ethics No: 1586/KEPK/STIKES-NHM/EC/II/2024). Findings showed 62.2% of respondents were inactive in posyandu, while 66.4% of toddlers had normal nutritional status. With a p-value of 0.094 (ρ > α = 0.05), the result indicated no significant influence. Recommendation: Parents should be encouraged to attend posyandu regularly, aided by cadres through reminders and nutrition education efforts.